2022
DOI: 10.1182/blood.2021013614
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into collagen binding by platelet receptor glycoprotein VI

Abstract: Glycoprotein VI (GPVI) mediates collagen-induced platelet activation after vascular damage, and is an important contributor to the onset of thrombosis, heart attack and stroke. Animal models of thrombosis have identified GPVI as a promising target for antithrombotic therapy. Although for many years the crystal structure of GPVI has been known, the essential details of its interaction with collagen have remained elusive. Here, we present crystal structures of the GPVI ectodomain bound to triple-helical collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…On the other hand, GPVI binds a site on collagen comprising of two collagen chains, with the core formed by the sequence motif OGPOGP. Likewise, this study confirms that GPVI binds sites in collagen created by two of the three triple-helix chains and canonical OGPOGP sequence motifs [ 41 ].…”
Section: Glycoprotein VI and Its Function In Hemostasissupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, GPVI binds a site on collagen comprising of two collagen chains, with the core formed by the sequence motif OGPOGP. Likewise, this study confirms that GPVI binds sites in collagen created by two of the three triple-helix chains and canonical OGPOGP sequence motifs [ 41 ].…”
Section: Glycoprotein VI and Its Function In Hemostasissupporting
confidence: 79%
“…In concordance with the above, the density of the GPVI receptor on the platelet surface is directly proportional to the response to collagen and platelet adhesion [ 40 ]. Recently, a structural analysis revealed that GPVI presents a collagen-binding site across the β-sheet of the D1 domain, which are the amino-acids Trp76, Arg38, and Glu40, essential residues for binding to fibrillar collagens and collagen-related peptides (CRPs) [ 41 ]. On the other hand, GPVI binds a site on collagen comprising of two collagen chains, with the core formed by the sequence motif OGPOGP.…”
Section: Glycoprotein VI and Its Function In Hemostasismentioning
confidence: 99%
“…The GPVI-CRP crystal structures (PDB ID: 5OU8 and 5OU9) reveal that the CRP-binding motif of GPVI is present within a groove on D1 with an orientation that allows the binding of multiple GPVIs along a single triple helix. 12 In the glenzocimab-GPVI co-crystal the variable domain of the Fab light chain bound to D2 lies directly in the path of the D1-bound CRP chain, thus preventing the binding of longer CRP or collagen chains (Figure 4 and supplemental video).…”
Section: Gpvismentioning
confidence: 99%
“…4 The crystal structures of the GPVI exodomain, with and without triple helical (GPO)n-containing collagen-related-peptide (CRP), have previously been solved revealing a dimer interface at D2 and the site of CRP binding at D1. 11,12 A major advance in our understanding of the role of GPVI was the discovery that it binds to fibrin(ogen). [13][14][15] Interactions between GPVI and fibrin and fibrinogen endow it with an important role in the growth and stability of a thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…Early platelet adhesion and activation are key factors for the development of IS inflammatory thrombosis. The main receptors that mediate platelet adhesion are glycoprotein (GP) VI and integrin α2β1, both of which bind to the GPIbα subunit of collagen and the GPIB-IX-V complex, which interact with the von Willebrand factor (vWF) ( Poulter et al, 2017 ; Constantinescu-Bercu et al, 2022 ; Feitsma et al, 2022 ). After endothelial injury, vWF interacts with GPIbα, thus causing platelets to decelerate on the fixed vWF ( Constantinescu-Bercu et al, 2022 ; Kanaji et al, 2022 ) and thereby contributing to platelet aggregation.…”
Section: Pathogenesis Of Ischemic Strokementioning
confidence: 99%